2015
DOI: 10.1007/s11999-015-4445-0
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Variation in Episode-of-care Payments for Primary TKA? An Analysis of Medicare Administrative Data

Abstract: Background Episode-of-care payments are defined as a single lump-sum payment for all services associated with a single medical event or surgery and are designed to incentivize efficiency and integration among providers and healthcare systems. A TKA is considered an exemplar for an episode-of-care payment model by many policymakers, but data describing variation payments between hospitals for TKA are extremely limited. Questions/purposes We asked: (1) How much variation is there between hospitals in episode-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 26 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…10 Findings from this current study is consistent with previously published literature on costs in TKA. [11][12][13][14][15][16][17][18] Cram et al 17 studied 167,186 patients from Medicare administrative databases who underwent primary TKAs in 2009 and found that mean Medicare payments for EOC increased from $19,633 for patients with 2 or fewer comorbidities to $27,578 for patients with 5 or more comorbidities (p < 0.0001). Li et al 12 also investigated Medicare payments for patients who underwent TKA in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…10 Findings from this current study is consistent with previously published literature on costs in TKA. [11][12][13][14][15][16][17][18] Cram et al 17 studied 167,186 patients from Medicare administrative databases who underwent primary TKAs in 2009 and found that mean Medicare payments for EOC increased from $19,633 for patients with 2 or fewer comorbidities to $27,578 for patients with 5 or more comorbidities (p < 0.0001). Li et al 12 also investigated Medicare payments for patients who underwent TKA in 2009.…”
Section: Discussionmentioning
confidence: 99%
“…4 Significant variation in spending for surgical procedures exists across US hospitals. 5 Variability in cost is explained by the post acute episode of care, 6,7 type of joint implant, 8 geographic region, 9 and type of medical center. 9 Age, [9][10][11][12][13] disease severity, 6,10,14-16 socioeconomic status and social determinants of health, 9,[17][18][19] and medical comorbidities are associated with increased LEJR costs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Variability in cost is explained by the post acute episode of care, 6,7 type of joint implant, 8 geographic region, 9 and type of medical center. 9 Age, [9][10][11][12][13] disease severity, 6,10,14-16 socioeconomic status and social determinants of health, 9,[17][18][19] and medical comorbidities are associated with increased LEJR costs. 9,11,[20][21][22][23][24][25] In an attempt to reduce cost variability, the Centers for Medicare & Medicaid Services (CMS) issued the Comprehensive Care for Joint Replacement (CJR) 26 rule mandating bundled payment for LEJR in 67 geographic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Total joint arthroplasty (TJA) has been identified as a procedure with substantial variations in inpatient and postacute care costs [3,10,28,33,39]. Consequently, several private and public payers have been testing alternative payment models in an effort to reduce costs, improve value, and emphasize quality in patients' transition from surgery to recovery [14,16,40].…”
Section: Introductionmentioning
confidence: 99%
“…As such, various bundled payments for TJA are increasing among private payers, such as insurance providers and employers [14,16,40]. Consequently, hospitals considering participating in such initiatives and involved in the TJA care cycle have sought to evaluate their specific service-component cost differences across each TJA episode of care and factors associated with episode payments [5,10,17].…”
Section: Introductionmentioning
confidence: 99%